Secularisations and Their Debates
VI, 235 p.
Keywords: This volume explores timely topics in contemporary political and social debates, including: the new atheisms, the debate between Habermas and the Pope on the fate of modernity, and the impact of new scientific developments on traditional religions. This book collects articles first presented at the Deakin University "World in Crisis" workshop, held November 2010 by leading Australasian philosophers and theologians. It addresses questions raised by the recent, much-touted return to religion, including possible reasons for the return and its practical, political, and intellectual prospects. Secularisation and Their Debates is not afraid to provide answers to such questions as: Is religion only ever a force of political reaction in modernity, or are there resources in it which progressive, even secular social movements, could engage with or adopt? Are the new atheisms, or on the opposite side, the new fundamentalisms, really novel phenomena, or has religion only ever been artificially sidelined in the modern Western states? Has modern liberalism only really been kidding itself about its non-doctrinal neutrality between different faiths, and if so, what should follow? This book will appeal to researchers in the philosophy of religion, social sciences, political philosophy, and anthropology.